Watercolor of Cottage Inn - Betty Guy:::Creator:::::::::::: (United Kingdom)
Watercolor of the Discove Cottage, England, done by Betty Guy. The cottage is where John and Elaine Steinbeck lived between 1959-02 & 1959-09 while he worked on his translation of Morte D'Arthur. Guy was an American artist, most notable for her work in watercolor landscapes. Copy in physical files is in black and white; the digital copy is in color.